PERANCANGAN SISTEM INFORMASI E-ARSIPBERBASIS WEB PADA KANTOR DESA SIKAMPUH - Daniel Rudjiono; Nadya Rahma Febrianar (LPPM Politeknik Pratama Kendal, 2026)
The rapid development of information technology has prompted institutions to transition from manual systems to digital ones. The Sikampuh Village Office still uses conventional methods in archiving incoming and outgoing letters, such as recording in an agenda book and storing documents in folders. This method creates various problems, including difficulties in locating documents, the risk of damage, and the potential loss of archives. This study aims to design a web-based e-archive information system that is valid and effective to support the archiving process in the Sikampuh Village Office. The research method employed is Research and Development (R&D), which involves problem identification, data collection, system design, design validation, testing, and product revision. The system was developed using PHP, MySQL, and Bootstrap, and can be accessed through an internet connection. Internal and external validation results show an average score of 3.3–3.4, categorized as highly valid. Effectiveness testing indicates an improvement in performance from 37.5% (old system) to 82.5% (new system). The e-archive system enhances document retrieval, improves archive security, and accelerates reporting